Musical Culture of Polish Benedictine Nuns in the 17th and 18th Centuries - Walter-Mazur, Magdalena (2018)
The study is the first monograph devoted to the musical culture of a female order in Poland. It is a result of in-depth research into musical, narrative, economic, and prosopographic sources surviving in libraries and archives. Focused on the musical practice of nuns, the book also points to the context of spirituality, morality, and culture of the post-Trident era. The author indicates the transformation of the musical activity of the nuns during the 17th and 18th century and discusses its various kinds: plainsong, Latin and Polish polyphonic song, polichoral, keyboard, vocal-instrumental and chamber music. She reflects on the role of music in liturgy and monastic events and in everyday life of cloistered women, describes the recruitment of musically gifted candidates, and the scriptorial activity of nuns.